2021
DOI: 10.3390/nu13030835
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oral Nutritional Supplements on Older People with Anorexia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Nutrition plays an important role in maintaining the overall health of older people. Inadequate intake may lead to impaired body function, higher morbidity, and mortality. Oral nutritional supplements (ONS) showed positive effect on the nutritional status of the elderly; however, systematic evidence is currently lacking on the effect of ONS on the elderly with anorexia. Aims: The current systematic review and meta-analysis included randomized controlled trial (RCT) articles to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 79 publications
0
15
0
1
Order By: Relevance
“…These in vitro results corroborate the effects of MP-enriched ice cream on BMD and BALP in postmenopausal women. In addition, we have developed and tested an enriched food which is more patient-accepted than powder and tablet formulations [ 50 ]. In addition, ice cream also contains calcium, a constituent mineral of bone [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These in vitro results corroborate the effects of MP-enriched ice cream on BMD and BALP in postmenopausal women. In addition, we have developed and tested an enriched food which is more patient-accepted than powder and tablet formulations [ 50 ]. In addition, ice cream also contains calcium, a constituent mineral of bone [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Sato et al reported that stroke patients who received higher energy intake (23.5 kcal/kg/day) during 7 days of hospitalization had higher activity daily living (ADL) at discharge and more patients discharged home than those with lower energy intake (12.4 kcal/kg/day) with p < 0.001 [15]. Research conducted by Li et al reported that oral nutritional supplementation significantly increased energy intake (p = 0.02) and increased appetite (p < 0.001), both in hospitalized patients and in the community, without reducing the amount of intake from the meal [16]. Patient compliance with the use of oral nutritional supplementation was also reported to be quite high (mean 78%) compared to other methods of nutritional support [17], [18].…”
Section: Discussionmentioning
confidence: 99%
“…Summary recommendations from an umbrella review suggest some benefits of ONS for increasing lean mass and body weight in older adults residing in the community 34 . More recently, ONS have been shown to be effective in enhancing appetite, energy intake, and body weight, compared with a standard diet or control product, in older adults with anorexia of aging 36 . Conversely, meta‐analysis–level data evaluating the effectiveness of treatment with ONS vs usual care in malnourished older adults found no significant gains in body weight, body mass index, or other measures of nutrition status 35 .…”
Section: Ons Vs Food‐based Approaches For Unintentional Weight Lossmentioning
confidence: 99%
“… 34 More recently, ONS have been shown to be effective in enhancing appetite, energy intake, and body weight, compared with a standard diet or control product, in older adults with anorexia of aging. 36 Conversely, meta‐analysis–level data evaluating the effectiveness of treatment with ONS vs usual care in malnourished older adults found no significant gains in body weight, body mass index, or other measures of nutrition status. 35 Alternatively, food‐based interventions for older adults supported improved energy and protein intakes but substantiation by body weight data were lacking.…”
Section: Ons Vs Food‐based Approaches For Unintentional Weight Lossmentioning
confidence: 99%